Using experimental designs to evaluate corrosion inhibitors in chemical cleaning - Sánchez Gómez, Miguel; Hernández, Yolanda; Ruiz, Omar (Rev. Téc. Fac. Ing. Univ. Zulia)
This paper studies the parameters affecting the efficiency of the corrosion inhibitors used in chemical cleaning for the removal of deposits in carbon steel equipment. Optimum values from the parameters indicate that the corrosion rate will be minimized. Experimental Analysis and Design Techniques were used to establish relationships between the factors under study (temperature and concentration) by using well-planned experiments designed to determine an experimental region consisting of values that could be used in the industry. SAE 1020 carbon steel rods (0.3 cm in diameter) were embedded in teflon and coupled to an electrode rotating at a speed of 3000 rpm to simulate fluid flow conditions. These rods were immersed in inhibited HCI solutions. Electrochemical tests were carried out using the calomel electrode as the reference electrode and the platinum one as an auxiliary electrode. Potentiodynamic curves were used to calculate the corrosion rate. The overall results show that temperature was the most important factor that increases the corrosion rate.